LESSON STUDY AND THE IMPROVEMENTS OF TEACHERS' PEDAGOGIC COMPETENCE IN TEACHING ENGLISH TO YOUNG LEARNERS - Mardiana, Primasari Nurul (2013)
This study is concerned with investigating the value of lesson study in teaching English to young learners and teachers' pedagogic competence. Four teachers of a non formal early childhood education in Bandung were involved as the subjects of this study. The purpose of this research is to investigate the value of lesson study on teachers' pedagogic competence through examining the practical problems faced by the teachers, the efforts to overcome the problems, and the changes as the evidence of improvements. This case study obtained the data by ways of observations, interviews, & focus group and analysed both qualitatively and quantitatively. The results show that teachers carried out the teaching job closer to what are required by the regulation, maximized the use of learning supports, used more appropriate strategies in teaching English to young learners, produced better English in quality & quantity, and became more confident than before. Generally this study has given an illustration of how the treatments which came up from the discussion could make the signficance to the teachers' quality in teaching English to young learners. Keywords: early childhood education, pedagogic competence, young learners.